The thymulin lactotropic axis in rodents: thymectomy, immunoneutralization and gene transfer studies - Martines, Eliana V. (2013)
Objectives: There is clear evidence on the existence of a thymus-pituitary axis which seems to be particularly important during perinatal life. In particular, the thymic peptide thymulin has been shown to be a relevant player in thymuspituitary communication. Our goal was to explore the effect of thymulin on circulating prolactin (PRL) levels in different animal models. To this end we undertook a series of experiments in rats and mice, implementing adult thymectomy, thymulin immunoneutralization in normal C57BL/6 mice and neonatal thymulin gene therapy in nude mice. Methods: We assessed the impact of the above manipulations on PRL secretion and lactotrope morphology by measuring serum PRL by radioimmunoassay and by performing morphometric analysis of the lactotropic cell population in the anterior pituitary gland. Results: Adult thymectomy in female rats slightly increased serum PRL, an effect that was partially reversed by thymulin gene therapy. In mice, thymulin immunoneutralization from birth to age 32 days reduced serum PRL both in males and females. Thymulin immunoneutralization induced a significant (p < 0.01) decrease in lactotrope cell density (CD) and volume density (VD) without changes in cell size (CS). Neonatal thymulin gene therapy markedly increased serum thymulin (p < 0.01) and lactotrope CD, CS and VD in nude mice of both sexes. Conclusions: Our findings suggest a modulatory effect of thymulin on the lactotrope cell population and on serum PRL, particularly during early life.